Struktura informacji reprezentującej wiedzę - Sobieska-Karpińska, Jadwiga; Żmigrodzki, Marcin (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The article explains the role of information structure in knowledge management in the context of information science. It defines information structure as a set of attributes describing content of a piece of information. Then levels and strength of information structure are analyzed, and the process of building information structure is resented. At the end it is concluded that information representing knowledge in modern enterprises is mainly weak structured. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 238-251